Effect of an in Service Training Program for Intensive Care Nursing Staff in Their Knowledge and Practice - Khartoum State 2014-2017 - Ashraf Abdelrhman Elbashir, (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Cardiopulmonary resuscitation is the emergency procedure used to salvage victims of cardiac and respiratory arrest. It should be carried out with great urgency to avoid permanent brain damage or even death that would result if the victim stays from 4 to 6 minutes without oxygen. The aim of study To assess the effectiveness of structured teaching program on the knowledge and skills of cardio pulmonary resuscitation among the nursing staff in the Khartoum Teaching, Ahmed Gasim, Omdurman Teaching, and the Khartoum North Teaching hospitals. Methods A quasi experimental design pretest/posttest for the same group. The study was conducted in the intensive care units in Khartoum hospitals. The study sample consisted of 100 nurses. Data was collected by a questionnaire and an observational checklist. The intervention program was in a form of lectures guidelines book. Data were analyzed using Statistical Packages for Social Sciences (SPSS). Results The study showed the knowledge grades before implementation of the program were, poor in 42%; good in 22% and very good in 36% of the participants. Whereas after implementation of the program knowledge grades became, 3% poor; 16% good and 81% very good, (p value 0.001). also the study revealed that, Nurses' skills before implementation program poor (57%) good (31%) very good (12%). Nurses' skills after implementation program poor (4%) good (18%) very good (78%), (P value 0.002). Conclusion The study concluded that educational program had a significant impact related to the improvement of the nurses’s knowledge and practice post application of the program.